Bioefficacy of Steinernema sp. as a Biocontrol Agent Against Spodoptera frugiperda Under Laboratory Conditions - Wagiyana; Imielda Yuli Hartika Sari; Bakhroini Habriantono; Ankardiansyah Pandu Pradana (Jurnal Sumberdaya Hayati, 2026)
Spodoptera frugiperda control in agricultural crops, particularly corn crops, is a major challenge. The bioefficacy of the entomopathogenic nematode Steinernema sp. in suppressing S. frugiperda larvae was studied in this work. The Steinernema sp. isolate was obtained from the Biological Control Agent Service Post in Sidodai, while the S. frugiperda isolate was propagated at the University of Jember's Plant Pest Laboratory. In bioefficacy evaluations, different doses of Steinernema sp. were applied to third-instar S. frugiperda larvae, and mortality rates, lethal time 50% (LT50), and infection rates were monitored over 120 hours. The findings indicated the ability of Steinernema sp. to cause mortality in S. frugiperda larvae. Mortality increased with time, showing effective pest suppression. Significant differences among Steinernema sp. doses indicated a density-dependent impact. Greater nematode populations resulted in lower LT50 values, indicating quicker mortality induction. Infection rates decreased over time at all doses, although the highest concentration of 1,000 IJ mL⁻¹ consistently had the highest infection rate. These data confirm the potential of Steinernema sp. as an environmentally friendly biological control agent for S. frugiperda in corn crops.